Primate microbiomes over time: Longitudinal answers to standing questions in microbiome research. Issue 10 (2nd April 2019) - Björk, Johannes R.; Dasari, Mauna; Grieneisen, Laura; Archie, Elizabeth A.
Abstract: To date, most insights into the processes shaping vertebrate gut microbiomes have emerged from studies with cross‐sectional designs. While this approach has been valuable, emerging time series analyses on vertebrate gut microbiomes show that gut microbial composition can change rapidly from 1 day to the next, with consequences for host physical functioning, health, and fitness. Hence, the next frontier of microbiome research will require longitudinal perspectives. Here we argue that primatologists, with their traditional focus on tracking the lives of individual animals and familiarity with longitudinal fecal sampling, are well positioned to conduct research at the forefront of gut microbiome dynamics. We begin by reviewing some of the most important ecological processes governing microbiome change over time, and briefly summarizing statistical challenges and approaches to microbiome time series analysis. We then introduce five questions of general interest to microbiome science where we think field‐based primate studies are especially well positioned to fill major gaps: (a) Do early life events shape gut microbiome composition in adulthood? (b) Do shifting social landscapes cause gut microbial change? (c) Are gut microbiome phenotypes heritable across variable environments? (d) Does the gut microbiome show signs of host aging? And (e) do gut microbiome composition and dynamics predict host health and fitness? For all of these questions, we highlight areas where primatologists are uniquely positioned to make substantial contributions. We review preliminary evidence, discuss possible study designs, and suggest future directions. Abstract : To date, most insights into the processes shaping vertebrate gut microbiomes have emerged from studies with cross‐sectional designs. While this approach has been valuable, emerging time series analyses on vertebrate gut microbiomes show that gut microbial composition can change rapidly from 1 day to the next, with consequences for host physical functioning, health, and fitness. Research Highlights: To date nearly all insights into the processes shaping vertebrate gut microbiomes have emerged from studies that have cross‐sectional designs, but emerging time series analyses show that gut microbiomes can change rapidly from 1 day to the next. Field‐based primate studies, owing to their focus on the lives of individual animals, and the relative ease of collecting longitudinal fecal samples from known animals, are better positioned to collect these data than studies of humans or other species. We propose five questions of general interest to microbiome science where field‐based primate studies are especially well positioned to fill major gaps. We review preliminary evidence, discuss possible study designs, and suggest future directions.